Questions Muslims ask : what Christians actually do (and don't) believe - Scott, Robert, 1974- (Downers Grove, Ill. : IVP Books ; [Grand Rapids, Michigan] : Distributed ... by Zondervan Pub. House, 2011)
Christians and Muslims don't understand each other very well. Muslims have often heard that Christians worship three gods, or that the Injil, the Christian Scripture, has been corrupted. How can Christians explain their faith in a way that Muslims can understand? In his work with Muslims in central London, Robert Scott has discovered that many are quite open to talking about matters of faith. In this thoughtful and respectful book, he explores common questions and objections his Muslim friends have discussed with him over the years. --from publisher description
How can we know an incomprehensible God?: Allahu Akbar! The God of the Bible is great! -- Don't Christians only do Sundays?: living each day for God -- What sort of god can be murdered?: the certain victory of Jesus the Messiah -- What sort of god can be born as a baby?: the word took on human form -- But don't Christians believe in three gods?: The personal and united God -- Where does Christianity end and western culture begin?: the multicultural gospel -- Hasn't the Bible been corrupted?: the trust worthiness of God's living and powerful word -- How can we be sure about God?: answers, assurance and hope.
"Published in England as Dear Abdullah."--t.p. verso.
Includes bibliographical references.
Keywords: Apologetics -- Miscellanea; Missions to Muslims; Christianity and other religions -- Islam; Islam -- Relations -- Christianity